Sosialisasi Pendewasaan Usia Perkawinan Sebagai Upaya Mengatasi Pernikahan Usia Anak pada Siswa MA Miftahul Ulum di Desa Gisting Atas - Sulastri Sulastri; Syafira Fahlupi; Imas Nurkholifah; Novrizal Saputra; Arif Julyansyah; Tegar Trisetiawan (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Early marriage is a marriage that takes place at an age below the productive age, which is less than 20 (twenty) years for women and less than 25 (twenty five) years for men. With the rampant early marriages that occur due to the mindset of the community that considers early marriage to be commonplace, especially for rural communities. To support the knowledge of MA Miftahululum students, students conducted socialization regarding the maturity of the age of marriage which was carried out targeting students of MA Miftahululum, Gisting Atas Village. This activity aims to increase student awareness regarding the maturity of the age of marriage. Through various educational activities, such as seminars and discussions, students are expected to be able to understand the consequences of the decision to marry at a young age. Education is one of the main keys to overcoming the problem of early marriage. By providing a good understanding of reproductive health, children's rights, and the importance of education, adolescents can be better prepared to face the challenges of life. In addition, reproductive health is also an important aspect that needs to be considered. Adolescents who marry early are at higher risk of experiencing health problems, such as complications during pregnancy and childbirth. The role of parents and society is also very important in supporting the maturity of the age of marriage.